Data files for the 2016 lahars at La Lumbre, Colima, Mexico - Walsh, Braden (Uppsala University, 2019)
Seismic data for lahars at Lumbre channel, Colima, Mexico recorded on a seismometer late 2016.

The dataset was originally published in DiVA and moved to SND in 2024.

Seismiska data för lahars vid Lumbre-kanalen, Colima, Mexiko, registrerade med en seismometer i slutet av 2016.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Data files for the 2016 lahars at La Lumbre, Colima, Mexico
Keywords: seismology; seismologi; Geophysics; Geofysik